Passive standing tests for the office diagnosis of postural tachycardia syndrome: New methodological considerations. Issue 4 (2nd October 2018) - Roma, Maria; Marden, Colleen L.; Rowe, Peter C.
ABSTRACT: Background: Passive standing tests are a first-line, practical means of assessing individuals with chronic orthostatic symptoms. Purpose: To identify the proportion reaching heart rate (HR) criteria for postural tachycardia syndrome (POTS) during a 10-minute passive standing test (PST) if measurement of the lowest supine HR incorporated a 2-minute period of post-test monitoring, rather than being restricted to the 5-minute pre-test values only, and to determine the proportion whose POTS would be missed by shorter periods upright. Methods: Consecutive individuals ≥ 12 years from 2008 to 2017 who presented with chronic fatigue or lightheadedness and whose PST met criteria for POTS. Results: Of the 93 enrolled (70% female, median age 17 years), the mean (SD) HR was higher in the 5 min supine before the 10 min upright than in the 2 min supine afterwards (67.6 [10.0] vs. 65.7 [10.9]; P = 0.01). Thirteen (14%; 95% CI, 7–21%) satisfied HR criteria for POTS using the supine HR from only the post-test period. The median time to reaching the HR criteria for POTS was 3 min. Of those reaching HR criteria, 53% (95% CI, 43–63%) would be missed by a 2-minute and 27% (95% CI, 19–37%) by a 5-minute test. Interpretation: More adolescents and young adults are diagnosed with POTS during a 10-minute PST when the definition of their lowest supine HR includes a 2-minute post-test measurement along with the conventional pre-test measure. A full 10 min of standing is required to avoid underdiagnosing POTS in both clinical and epidemiologic studies.